BERYLLIUM-10 CONCENTRATIONS OF TEKTITES FROM THE IVORY COAST AND FROM CENTRAL EUROPE: EVIDENCE FOR NEAR-SURFACE RESIDENCE OF PRECURSOR MATERIALS - Serefiddin F.; Herzog G.F.; Koeberl C. (My University, 2007)
By using accelerator mass spectrometry, we measured 10Be (T1/2 = 1.5 Ma) concentrations in nine Ivory Coast (IVC) tektites, in six soil samples collected near the Bosumtwi impact crater, the likely source region, and in a depth profile taken through a 23 g moldavite. In the core of the moldavite sample we also measured an upper limit on the 36Cl (T1/2 = 0.3 My) concentration. The average 10Be concentration in IVC tektites of (22 ± 11) × 106 atom/g exceeds reasonable limits for a meteoritic component or cosmic-ray production in situ after tektite formation. The 10Be must be meteoric, which implies that IVC tektites formed from soils or sediments. Corrected to the time of formation (ToF) 1.07 Ma ago and for a small in situ component, the average 10Be concentration of (35 ± 7) × 106 atom/g (1 - σ mean) is considerably lower than those of contemporary Bosumtwi soils, ~250 × 106 atom/g, or of Australasian tektites at their ToF, 0.8 Ma B.P. near Lake Bosumtwi today the soil column is only ~1 m thick. If the landscape was similar 1.07 Ma ago, then the total thickness of the tektite formation zone probably did not exceed 10 m. With increasing depth below the surface of the moldavite, the 10Be concentrations decrease rapidly owing to the presence of a surface component, probably of recent origin. The main interior mass of the sample contains ~0.8 × 106 atom 10Be/g and fewer than 0.1 × 106 atom 36Cl/g, little of which can be meteoritic. Although not definitive, consideration of several possible cosmic-ray exposure histories suggests that about half the interior 10Be has a meteoric origin, which if corrected to the time of formation yields a concentration compatible with those measured in typical contemporary soils. The observations are consistent with the formation of three of the four main tektite groups from surface soils or sediments. © 2007 Elsevier Inc. All rights reserved.